Hubungan Kecukupan dan Mineral Pakan dengan Tingkat Kebuntingan Sapi Bali dan Perbedaannya antar Wilayah Dataran Tinggi, Sedang dan Rendah di Provinsi Jambi - Fachroerrozi Hoesni; Firmansyah Firmansyah; Afzalani Afzalani; Farizal Farizal (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The purpose of this study was to analyze the close relationship between feed adequacy and forage minerals with the pregnancy rate of Bali cattle in Jambi Province and to analyze differences in feed and mineral adequacy and the success of pregnancy in Bali cattle between high, medium and lowland areas in Jambi Province. The research method used in this research is survey and laboratory, with Stratified Random Sampling sampling technique, namely the highland area is represented by Kerinci Regency, the medium-land area is represented by Tebo Regency and the lowland area is represented by Tanjung Jabung Barat Regency. To analyze the close relationship between feed adequacy and feed minerals with pregnancy rates for Bali cattle in Jambi Province, Pearson Correlation, Kendall's tau_b, and Spearman's rho analysis were used. To analyze the differences in the adequacy of feed and mineral feed and the pregnancy rate of Bali cattle between high, medium and lowland areas in Jambi Province, the average difference test was used. The adequacy of cattle feed in the highlands, medium and lowlands in Jambi Province averaged 107.04% ± 6.91. Bali cattle pregnancy rate in the highlands, medium and low in Jambi Province is an average of 74.60 ± 25.60. This study concludes that the pregnancy rate of Bali cattle varies between high, medium and lowland areas in Jambi Province with an average of good categories. There is a significant correlation between the mineral content of feed in the form of Zn and Se and P with the pregnancy rate of Bali cattle in Jambi Province. There is a significant relationship between blood mineral content in the form of Zn, Se and Mg with the pregnancy rate of Bali cattle in Jambi Province